Human RPS19, the gene mutated in Diamond-Blackfan anemia, encodes a ribosomal protein required for the maturation of 40S ribosomal subunits - Flygare, Johan (American Society of Hematology, 2007)
Diamond-Blackfan anemia (DBA) typically presents with red blood cell aplasia that usually manifests in the first year of life. The only gene currently known to be mutated in DBA encodes ribosomal protein S19 (RPS19). Previous studies have shown that the yeast RPS19 protein is required for a specific step in the maturation of 40S ribosomal subunits. Our objective here was to determine whether the human RPS19 protein functions at a similar step in 40S subunit maturation. Studies where RPS19 expression is reduced by siRNA in the hematopoietic cell line, TF-1, show that human RPS19 is also required for a specific step in the maturation of 40S ribosomal subunits. This maturation defect can be monitored by studying rRNA-processing intermediates along the ribosome synthesis pathway. Analysis of these intermediates in CD34(−) cells from the bone marrow of patients with DBA harboring mutations in RPS19 revealed a pre-rRNA–processing defect similar to that observed in TF-1 cells where RPS19 expression was reduced. This defect was observed to a lesser extent in CD34(+) cells from patients with DBA who have mutations in RPS19.